Ecological Aspects of the Assessment of Quality of Life - Ryumina, Yelena Viktorovna (Economy of Regions, 2016)
The article is devoted to the search of indicators, which reflect the ecological conditions and environmental behaviour and can be used for economic analysis. This environmental and economic issue still remains unsolved. The indicators of the emissions of harmful substances into the atmosphere and water objects, which are used in many economic works, characterize the future impact on the environment and cannot adequately reflect its state. From the ecologists’ point of view, the result of the environmental monitoring are, in particular, the indicators of the tests of air and water exceeding MPC (maximum permissible concentration) in a total number of the studied tests as a percentage. They have been already included in a number of official statistical bulletins. The paper shows their advantages for a concise accounting of a state of the environment in economic. The regional values of the chosen indicators are studied and various hypotheses of their strong differentiation are analyzed. The introduction of the ecological component to the indicators of quality of life as well as to the human development index is especially important at present time. The authors propose to use the indicator of a share of the negative tests of water and air as an additional fourth component in the human development index. The results of the calculation of the ecologically corrected index of human development for all entities of the Russian Federation are presented. It differs significantly for a number of regions from the traditional index of human development.